2014
DOI: 10.3389/fneng.2014.00023
|View full text |Cite
|
Sign up to set email alerts
|

Tracking single units in chronic, large scale, neural recordings for brain machine interface applications

Abstract: In the study of population coding in neurobiological systems, tracking unit identity may be critical to assess possible changes in the coding properties of neuronal constituents over prolonged periods of time. Ensuring unit stability is even more critical for reliable neural decoding of motor variables in intra-cortically controlled brain-machine interfaces (BMIs). Variability in intrinsic spike patterns, tuning characteristics, and single-unit identity over chronic use is a major challenge to maintaining this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…For example, using such a metric in studies of plasticity would lead to biased results (an underestimate of receptive field changes). To determine which recorded units are stable, therefore, a method based solely on waveform shapes should be used, such as those proposed by Tolias et al (2007), or Eleryan et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…For example, using such a metric in studies of plasticity would lead to biased results (an underestimate of receptive field changes). To determine which recorded units are stable, therefore, a method based solely on waveform shapes should be used, such as those proposed by Tolias et al (2007), or Eleryan et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…Since a typical decoder does not assign the same weights to all units, it may be desirable – from a pragmatic standpoint – to have more unit contributions to the computation of the decode. This can help in maintaining a decoder fixed across multiple days – even if some of the decoder units disappear for a few days ( Heliot et al , 2010; Eleryan et al , 2014). A unit’s contribution to the decode can be quantified in terms of its output z i ( t ).…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Using recordings from ‘stable’ populations of M1 neurons [39], units were divided into a number of non-overlapping clusters of functionally connected neurons – as measured by spike train correlations during periods of spontaneous activity [72]. An unsupervised, non-biomimetic decoder was built from offline analysis of spontaneous neural activity to enable the monkeys to control multiple DOFs [40].…”
Section: Plasticity Associated With Uni-directional Bmismentioning
confidence: 99%
“…As such, a stable transformation not only requires fixing the decoder mapping, but also assigning units to the BMI that have stationary spike waveform shapes that does not alter the day-to-day spike sorting outcome. Only a few neurons (on the order of tens), however, can be stably isolated across a period of days to weeks in typical chronic microelectrode recordings [39, 41, 76, 89-91], although Taylor et al empirically reported maintaining stability of neurons—as determined by their tuning properties to overt movement kinematics—for ~3 years (Taylor, Tillery et al 2002). Consequently, with few exceptions [92], most BMI studies to date rely on identification of new units and decoder recalibration before each session.…”
Section: Plasticity Associated With Uni-directional Bmismentioning
confidence: 99%
See 1 more Smart Citation